2021
DOI: 10.3390/jcm10173814
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Screening for Gestational Diabetes Mellitus in Twin Pregnancies

Abstract: We previously reported a logistic regression model for prediction of GDM from maternal characteristics and medical history in 75,161 singleton pregnancies. In this study of 1376 twin and 13,760 singleton pregnancies recruited at 11–13 weeks’ gestation, we extend the model to include terms for twin pregnancies. We found the respective odds of GDM in dichorionic and monochorionic twin pregnancies to be 1.36 (95% CI: 1.02–1.81) and 2.78 (95% CI: 1.72–4.48) times higher than in singleton pregnancies. In both singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Other models for the early prediction of GDM have not been as effective as the predictive models introduced above [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Other models for the early prediction of GDM have not been as effective as the predictive models introduced above [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Yong et al reported that in women of older age that started their pregnancy while being overweight or obese, the risk for GDM increased by 2.5 times, while gaining excess weight during pregnancy aggravated these odds [ 31 ]. Moreover, in a study conducted by Buerger et al, the authors evaluated the risk for GDM in singleton and twin pregnancies [ 32 ]. The odds were higher with advancing MA, increased weight and birthweight z-score from previous pregnancy, in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…The authors applied this information in the development of a screening model for GDM; therefore, setting the FPR at 10% and 20% for singleton pregnancies, the detection rates were 42.8% and 58%, respectively. The screening accuracy of the model by Buerger et al may be overestimated as the authors declare that their large sized control group may have included women with undiagnosed GDM, as OGTT was not applied in all pregnancies [ 32 ]. Likewise, in a predictive model used by Shen at al., which computed the maternal characteristics and obstetric history of pregnant women in screening for GDM, at FPR of 10% and 20%, the detection rates were 35.6% and 53%, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous large-for-gestational-age baby is a recognized risk factor for subsequent GDM [9, 30, 36], while the association between the standardized birth weight corrected for gestational age in a previous pregnancy and the risk of GDM has not been clearly described in the literature. Only two previous studies have reported on the relationship between birth weight Z -score of last pregnancy and risk of GDM, and both studies have demonstrated that the birth weight Z -score of last pregnancy is an independent predictor for the screening of GDM after adjusting for other maternal characteristics [36, 37]. The present study has demonstrated that for every unit increase of birth weight Z -score of last pregnancy from the mean ( Z -score 0) there is a 23% increase in the risk of GDM (OR 1.23, 95% CI: 1.10–1.37); in other words, the risk of GDM is not only limited to previous history of macrosomia or large for gestational age but also increases with birth weight Z -score of last pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Syngelaki et al [36] demonstrated that maternal age, weight, height, racial origin, family history of diabetes mellitus, use of ovulation drugs, previous birth weight, and previous history of GDM were significant first trimester predictors of subsequent development of GDM [36]. When utilizing this model for the screening of GDM in singleton pregnancies, at 10% and 20% FPR, the detection rates were 42.8% and 58.0%, respectively [37]. Our results have shown comparable predictive performance utilizing maternal characteristics and obstetric history (model 3), with detection rates of 35.6% (95% CI: 32.3-41.7) and 53.0% (95% CI: 48.2-57.7) at 10% and 20% FPR, respectively.…”
Section: Discussionmentioning
confidence: 99%